Análise da distribuição espacial da arrecadação do imposto predial territorial urbano em Goiânia-GO (2010-2014) - Aragão , Ana Luísa Santana (2016)
One of the ways to understand the process of organization of the urban space is to analyze the real estate revenues as the Municipal Real Estate Tax known in Brazil as IPTU. This tax beyond serving for urban maintenance, accomplishes extra fiscal functions which refer to tax justice search. The extra fiscal attributes are related to the social function of the urban property, aspects of tax distribuition, income distribuition etc. The IPTU, revenue of high visibility, does not always have its collection proportional to the needs of urban maintenance of the municipalities and not always accomplish its social function. It happens for administrative incapacity, wide variability in local legislations as the collection criteria or absence of instruments, as the Plant of Generic Values and real estate register, which are basis for an efficient collection by the townships. This work aims to analyze the spatial distribution of the IPTU collection in the municipality of Goiânia between 2010 and 2014, to understand the process of urban space organization. The first chapter presents an discussion about space, showing how this category can contribute for the analysis which refer to the use and regulation of the urban land. The work also presents an overview of the municipal revenues in Brazil as well the collection and distribution differently of the IPTU in the Brazilian municipalities. The collection of IPTU, in Brazil, is presented heterogeneously by the mode of collection and consequently impacts on the revenues of the municipalities. One of the problems linked to the low collection is related to the outdating of the Plant of Generic Values and real estate register. The organization and the production of space involve essential agents to understand how Goiânia developed itself and, in this scope of discussion, the second chapter point the agents which interfered in the process of occupation in the capital. For the comprehension of the relation between land market and habitation process in the current municipal legislation, we analyze laws and municipal decrees based on the Master Plan of Goiânia. The history of the collection of IPTU in Goiânia, in the opening of the third chapter, shows this history may reflect the advances and regresses of the urban policy in the capital considering, as an example that the tax progressivity appears in the municipal legislation of 1964. We approached laws and decrees related to the IPTU of the capital for this investigation. The data for the analysis of the evolution of the collection of IPTU between 2010 and 2014 were available by the Agency of Finances of Goiânia (Sefin). We found that the IPTU collection could be optimized if the real estate plant of values were updated yearly based in a real estate register equivalent to the current reality of the cadastral unit. Also we found that the mode of collection of the tax in Goiânia little favors the tax justice in view of the differences between the fiscal zones, between the neighborhoods which compose them and between the cadastral units of the same neighborhood.